1996
DOI: 10.2307/4088899
|View full text |Cite
|
Sign up to set email alerts
|

Within- and Among-Year Effects of Cold Fronts on Migrating Raptors at Hawk Mountain, Pennsylvania, 1934-1991

Abstract: ABsTRAcr.-Cold-front passage has long been associated with southbound raptor migration in northeastern North America. We used Hawk Mountain Sanctuary's 55-year database to calculate abundance indices of 14 raptor species at the site. These indices, together with data taken from coincidental U.S. Department of Commerce daily weather maps, were used to investigate the extent to which raptor migration at Hawk Mountain is associated with the passage of cold fronts. Daily abundance indices for 12 of 14 raptor speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 17 publications
0
42
1
2
Order By: Relevance
“…Richardson (1978) and Allen et al (1996) found migration rates to peak the day after a cold front's passage. We believe differences in the frequency of cold fronts to be the primary factor behind this discrepancy.…”
Section: Why Might the Effects Of Cold Fronts In Idaho Contrast With mentioning
confidence: 99%
See 4 more Smart Citations
“…Richardson (1978) and Allen et al (1996) found migration rates to peak the day after a cold front's passage. We believe differences in the frequency of cold fronts to be the primary factor behind this discrepancy.…”
Section: Why Might the Effects Of Cold Fronts In Idaho Contrast With mentioning
confidence: 99%
“…Following Millsap and Zook (1983), Hall et al (1992), and Allen et al (1996), we determined passages of cold fronts by analyzing synoptic weather maps obtained from the National Oceanic and Atmospheric Administration's (NOAA) Daily Weather Map series (U.S. Department of Commerce 2010a). We interpolated the timing of each front through examination of subsequent daily maps.…”
Section: Cold Frontsmentioning
confidence: 99%
See 3 more Smart Citations